Pendampingan Pembuatan Absensi Berbasis IoT Di Kantor Desa Keroya - Yulia Rosdiana, Nika; Arbi Mabruri; Leowaldi; Puspa Nilasari; Rido Nanda Pranggana; Nurhidayati; Dwi Rahayu Susanti (Universitas Hamzanwadi, 2025)
Abstract: The village employee attendance system using RFID and NodeMCU based on Telegram is designed to automate the employee attendance recording process. This system utilizes RFID (Radio Frequency Identification) technology and NodeMCU (ESP8266) to read RFID cards as employee identifiers. Attendance data is then automatically sent through a Telegram bot. NodeMCU acts as the RFID reader and message sender to the Telegram bot, while the Telegram bot records the employee’s attendance time and provides confirmation of attendance. During testing, when an employee scans a valid RFID card, the system sends a success message to Telegram, and the buzzer sounds for 2 seconds as an indicator. Conversely, if the card is invalid, a failure message is sent, and the buzzer sounds briefly. This system enhances the efficiency of attendance recording, reduces manual entry errors, and allows real-time management of attendance data. As a result, it not only simplifies the attendance process but also allows integration with larger attendance management systems.